The Influence of Internship Experience and Soft Skills on Work Readiness Mediated By Self-Efficacy - Wita Syawitri; Ikram Yakin; Ahmad Shalahuddin; Endah Mayasari (Krisnadwipayana International Journal of Management Studies, 2024)
Generation Z is the young age group that dominates the number of Open Unemployment Rate (OUR) in 2024 in Indonesia. In this situation, students and graduates who are potential future employees must prepare themselves with good work readiness by the skills needed in the workplace. This research examines how in Indonesian Generation Z self-efficacy mediates internship experience and soft skills regarding work readiness. The research population is all Generation Z with status as final-year students and fresh undergraduate graduates in Indonesia. Information was gathered using an online questionnaire via Google Forms, a sampling technique, and a purposive sampling approach. The results showed that internship experience positively and significantly affects work readiness and self-efficacy. Soft skills have been proven to positively and significantly impact work readiness and self-efficacy, while self-efficacy demonstrates a positive and significant impact regarding work readiness. Self-efficacy as mediation is proven to positively and significantly affect the connection of internship experience to work readiness, along with the between soft skills and work readiness.